Molecular mechanisms of stomatal closure in response to rising vapour pressure deficit. Issue 2 (29th July 2021) - Jalakas, Pirko; Takahashi, Yohei; Waadt, Rainer; Schroeder, Julian I.; Merilo, Ebe
Summary: Vapour pressure deficit (VPD), the difference between the saturation and actual air vapour pressures, indicates the level of atmospheric drought and evaporative pressure on plants. VPD increases during climate change due to changes in air temperature and relative humidity. Rising VPD induces stomatal closure to counteract the VPD‐mediated evaporative water loss from plants. There are important gaps in our understanding of the molecular VPD‐sensing and signalling mechanisms in stomatal guard cells. Here, we discuss recent advances, research directions and open questions with respect to the three components that participate in VPD‐induced stomatal closure in Arabidopsis, including: (1) abscisic acid (ABA)‐dependent and (2) ABA‐independent regulation of the protein kinase OPEN STOMATA 1 (OST1), and (3) the passive hydraulic stomatal response. In the ABA‐dependent component, two models are proposed: ABA may be rapidly synthesised or its basal levels may be involved in the stomatal VPD response. Further studies on stomatal VPD signalling should clarify: (1) whether OST1 activation above basal activity is needed for VPD responses, (2) which components are involved in ABA‐independent regulation of OST1, (3) the role of other potential OST1 targets in VPD signalling, and (4) to which extent OST1 contributes to stomatal VPD sensitivity in other plant species.